Isotopic ordering in atmospheric O2 as a tracer of ozone photochemistry and the tropical atmosphere. Issue 20 (26th October 2016) - Yeung, Laurence Y.; Murray, Lee T.; Ash, Jeanine L.; Young, Edward D.; Boering, Kristie A.; Atlas, Elliot L.; Schauffler, Sue M.; Lueb, Richard A.; Langenfelds, Ray L.; Krummel, Paul. B.; Steele, L. Paul; Eastham, Sebastian D.
Abstract: The distribution of isotopes within O2 molecules can be rapidly altered when they react with atomic oxygen. This mechanism is globally important: while other contributions to the global budget of O2 impart isotopic signatures, the O( 3 P ) + O2 reaction resets all such signatures in the atmosphere on subdecadal timescales. Consequently, the isotopic distribution within O2 is determined by O3 photochemistry and the circulation patterns that control where that photochemistry occurs. The variability of isotopic ordering in O2 has not been established, however. We present new measurements of 18 O 18 O in air (reported as Δ36 values) from the surface to 33 km altitude. They confirm the basic features of the clumped‐isotope budget of O2 : Stratospheric air has higher Δ36 values than tropospheric air (i.e., more 18 O 18 O), reflecting colder temperatures and fast photochemical cycling of O3 . Lower Δ36 values in the troposphere arise from photochemistry at warmer temperatures balanced by the influx of high‐Δ36 air from the stratosphere. These observations agree with predictions derived from the GEOS‐Chem chemical transport model, which provides additional insight. We find a link between tropical circulation patterns and regions where Δ36 values are reset in the troposphere. The dynamics of these regions influences lapse rates, vertical and horizontal patterns of O2 reordering, and thus the isotopic distribution toward which O2 is driven in the troposphere. Temporal variations in Δ36 values at the surface should therefore reflect changes in tropospheric temperatures, photochemistry, and circulation. Our results suggest that the tropospheric O3 burden has remained within a ±10% range since 1978. Key Points: O3 photochemistry and temperature control clumped isotopes in atmospheric O2 Stratospheric and tropospheric Δ36 signatures are distinct Circulation‐sensitive distribution of tropospheric O3 controls tropospheric Δ36